The effect of illness perception on psychosocial adjustment of patients with breast cancer and their spouses: actor–partner independence model - Yan-feng Wang; An-kang Liu; Jin-zhen Dai; Ji-ping Zhang; Hui-hua Chen; Xiao-hao Jiang; Lu Tang; Yong-yue He; Qiao-hong Yang (BMC Psychology, 2024)
Abstract Objective With the increase in the prevalence rate and improvements in the survival of breast cancer patients, there is a growing interest in understanding the level of psychosocial adjustment in these patients. The study aimed to describe the illness perception and psychosocial adjustment levels of both breast cancer patients and their spouses, to use the Actor-Partner Interdependence Model (APIM) to clarify the actor-partner relationships between spouses, and to explore the impact of illness perception on psychosocial adjustment to the disease within the joint actions of both spouses. Methods A total of 216 female patients with breast cancer and their spouses participated in the study. They were selected from two tertiary hospitals in Guangdong Province, China from October 2022 to May 2023 using a convenience sampling method. The participants were assessed using the Brief Illness Perception Questionnaire and the Psychosocial Adjustment to Illness Scale to examine the relationship between illness perception and psychosocial adjustment. AMOS24.0 was used to test and analyze the actor-partner interdependence model. Results The illness perception score (57.75 ± 10.91) was slightly higher than that of the spouse (57.10 ± 11.00), and the psychosocial adjustment score (64.67 ± 6.33) was slightly lower than that of the spouse (64.76 ± 7.49). The results of the actor-partner interdependence model indicated that there was a couple partner between breast cancer patients and their spouses: the spouse’s illness perception significantly affected the patient’s psychosocial adjustment (β = 0.095, p = 0.015); the patient’s illness perception also significantly affected the spouse’s psychosocial adjustment (β = 0.106, p = 0.033). Among them, the patient’s psychosocial adjustment was found to be related to the patient’s illness comprehensibility or coherence of illness (β = 0.433, p = 0.009), the spouse’s emotional illness representation (β = 0.218, p = 0.037), and the spouse’s illness comprehensibility or coherence of illness (β = 0.416, p = 0.007), while the spouse’s psychosocial adjustment was only related to the spouse’s illness comprehensibility or coherence of illness (β = 0.528, p = 0.007). Conclusions The psychosocial adjustment of breast cancer patients is affected by both their own and spouse’s illness perception. Therefore, in the future, the healthcare staff can implement early psychological interventions for patients diagnosed with breast cancer and their spouses as a unit to promote the psychosocial adjustment of them.